2010
DOI: 10.1007/s11999-010-1363-z
|View full text |Cite
|
Sign up to set email alerts
|

The Scarf Osteotomy: A Salvage Procedure for Recurrent Hallux Valgus in Selected Cases

Abstract: Background The Scarf osteotomy was described as a technique to correct a metatarsus primus varus in primary hallux valgus surgery, but it is unclear whether the technique could correct recurrent hallux valgus when an initial procedure failed to provide any or an adequate lateral displacement of the metatarsal head. Questions/purposes We asked whether the Scarf osteotomy could reduce pain, improve the AOFAS score, reduce the deformity, and prevent further recurrence when used as a revision procedure. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Function after MTP1 arthrodesis was found to be globally satisfying and durable in a study by Groulier et al [6]. Most series of Scarf osteotomy and MTP1 arthrodesis use the AOFAS score to evaluate functional criteria by comparing global preoperative and postoperative scores: the increase is comparable in all series with a gain of approximately 30 points [4,19,[22][23][24][25]. Nevertheless, the score items are not usually listed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Function after MTP1 arthrodesis was found to be globally satisfying and durable in a study by Groulier et al [6]. Most series of Scarf osteotomy and MTP1 arthrodesis use the AOFAS score to evaluate functional criteria by comparing global preoperative and postoperative scores: the increase is comparable in all series with a gain of approximately 30 points [4,19,[22][23][24][25]. Nevertheless, the score items are not usually listed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Although it allows correction of a metatarsus primus varus deformity in primary HV, it was uncertain if a Scarf osteotomy alone would allow correction of both metatarsal primus varus and the DMAA deformity. In appropriately selected patients, Bock et al suggested that, as a revision procedure, the Scarf osteotomy had a good outcome of clinically and radiographically corrected recurrent HV recurrence in most patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Pour l'arthrodèse, il est rapporté des erreurs de positionnement dans 3 à 20 % des cas [6], une surcharge de l'articulation interphalangienne dans 5 % [7] [4,19,[22][23][24][25]. Toutefois, généralement les items du score ne sont pas détaillés.…”
Section: Activités Pratiquéesunclassified